Academic Grit, Interest, and Technological Attitudes as Predictors of Learners’ Performance - Verson, John Michael; Potane, Joel (Journal of Interdisciplinary Perspectives, 2025)
As learning environments continue to evolve, it is essential to understand the psychosocial and technological factors that influence learners’ academic success. This study examined the predictive roles of academic grit, academic interest, and technological attitudes on learners’ performance in General Mathematics among 104 randomly selected Grade 11 STEM and ABM learners in a public school in Misamis Oriental. Using a descriptive-correlational design and both descriptive and inferential analyses, results revealed that learners demonstrated high levels of academic grit (M = 4.11, SD = 0.46) and positive technological attitudes (M = 3.98, SD = 0.53). In contrast, their academic interest was moderate (M = 3.42, SD = 0.51). Regression analysis revealed that academic grit (β = 0.247, p = .005) and technological attitude (β = 0.220, p = .020) were significant predictors of learners' mathematics performance, collectively explaining 9.8% of the variance (adjusted R² = 0.098). Conversely, academic interest did not significantly predict performance (p > .05). The findings suggest that perseverance and adaptability to digital tools contribute more strongly to academic achievement than interest alone. Hence, interventions that foster grit and promote purposeful technology integration may enhance learners’ mathematical proficiency and overall academic resilience.